Penerapan model pembelajaran Direct Instruction dipadukan metode Fish Bowl guna meningkatkan sikap sosial siswa kelas V SDN Teluk Tiram 2 Banjarmasin - Rahidatul Laila Agustina; Rifda Mardian Arif; Yudha Adrian (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
This study aims to find out how the increase in social attitudes using Direct Instruction learning methods combined with Fish Bowl in class V students of Teluk Tiram 2 SDN Banjarmasin The research method used is the research used is action research in the form of Classroom Action Research . The PTK model carried out in this study is collaborative CAR. In this PTK researchers as participant observers and collaborations with fifth grade teachers of Teluk Tiram SDN 2. In this study, researchers act as key instruments because researchers who design, collect data, analyze data, draw conclusions, and make reports, while the implementation of teaching is left to the fifth grade teacher at SDN Teluk Tiram 2. The subjects in this study were all students in grade V SDN Teluk Tiram 2, which numbered 20 people. The observation results of students' social attitudes showed an increase from the first cycle only gained 40.21%, increasing to 48.07% in the second cycle. Based on these descriptions, it can be concluded that the application of the Direct Instruction learning model combined with the Fish Bowl method can improve students' social attitudes at each meeting while carrying out learning